Graded Maximal Exercise Testing to Assess Mouse Cardio-Metabolic Phenotypes - Petrosino, Jennifer M.; Heiss, Valerie J.; Maurya, Santosh K.; Kalyanasundaram, Anuradha; Periasamy, Muthu; LaFountain, Richard A.; Wilson, Jacob M.; Simonetti, Orlando P.; Ziouzenkova, Ouliana (PLOS ONE, 2016)
Functional assessments of cardiovascular fitness (CVF) are needed to establish animal models of dysfunction, test the effects of novel therapeutics, and establish the cardio-metabolic phenotype of mice. In humans, the graded maximal exercise test (GXT) is a standardized diagnostic for assessing CVF and mortality risk. These tests, which consist of concurrent staged increases in running speed and inclination, provide diagnostic cardio-metabolic parameters, such as, VO2max, anaerobic threshold, and metabolic crossover. Unlike the human-GXT, published mouse treadmill tests have set, not staged, increases in inclination as speed progress until exhaustion (PXT). Additionally, they often lack multiple cardio-metabolic parameters. Here, we developed a mouse-GXT with the intent of improving mouse-exercise testing sensitivity and developing translatable parameters to assess CVF in healthy and dysfunctional mice. The mouse-GXT, like the human-GXT, incorporated staged increases in inclination, speed, and intensity; and, was designed by considering imitations of the PXT and differences between human and mouse physiology. The mouse-GXT and PXTs were both tested in healthy mice (C57BL/6J, FVBN/J) to determine their ability to identify cardio-metabolic parameters (anaerobic threshold, VO2max, metabolic crossover) observed in human-GXTs. Next, theses assays were tested on established diet-induced (obese-C57BL/6J) and genetic (cardiac isoform Casq2-/-) models of cardiovascular dysfunction. Results showed that both tests reported VO2max and provided reproducible data about performance. Only the mouse-GXT reproducibly identified anaerobic threshold, metabolic crossover, and detected impaired CVF in dysfunctional models. Our findings demonstrated that the mouse-GXT is a sensitive, non-invasive, and cost-effective method for assessing CVF in mice. This new test can be used as a functional assessment to determine the cardio-metabolic phenotype of various animal models or the effects of novel therapeutics.